2019
DOI: 10.1093/mnras/stz2609
|View full text |Cite
|
Sign up to set email alerts
|

Search for RR Lyrae stars in DES ultrafaint systems: Grus I, Kim 2, Phoenix II, and Grus II

Abstract: This work presents the first search for RR Lyrae stars (RRLs) in four of the ultra-faint systems imaged by the Dark Energy Survey (DES) using SOAR/Goodman and Blanco/DECam imagers. We have detected two RRLs in the field of Grus I, none in Kim 2, one in Phoenix II, and four in Grus II. With the detection of these stars, we accurately determine the distance moduli for these ultra-faint dwarf satellite galaxies; µ 0 =20.51±0.10 mag (D =127±6 kpc) for Grus I and µ 0 =20.01±0.10 mag (D =100±5 kpc) for Phoenix II. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 148 publications
(163 reference statements)
5
37
0
Order By: Relevance
“…Moreover, the stream stars are ∼10kpc closer than GruII (Koposov et al 2019). The difference in distance and velocity between GruII and the Orphan Stream likely rules out any connection between the two (Martínez-Vázquez et al 2019). In our spectroscopic data set, we find two stars close to the expected velocity and proper motion of the stream, DESJ220441.57−462244.8 and DESJ220458.78−462710.6.…”
Section: A Tucana Group?mentioning
confidence: 60%
“…Moreover, the stream stars are ∼10kpc closer than GruII (Koposov et al 2019). The difference in distance and velocity between GruII and the Orphan Stream likely rules out any connection between the two (Martínez-Vázquez et al 2019). In our spectroscopic data set, we find two stars close to the expected velocity and proper motion of the stream, DESJ220441.57−462244.8 and DESJ220458.78−462710.6.…”
Section: A Tucana Group?mentioning
confidence: 60%
“…In Figure 11 we show the number of known RRLs in each UFD as a function of their M V . The red line is the power-law fit that Martínez-Vázquez et al (2019) obtained using data for all dwarf satellite galaxies around the Milky Way and Andromeda in addition to isolated galaxies and two Sculptor group dwarfs, spanning near 17 magnitudes in M V . The fit was done using only galaxies in which a search for RRLs has been carried out in areas enclosing > 2 r h (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the Chenab stream (Shipp et al 2018) cohabits the same region of the sky as Grus II. Martínez-Vázquez et al (2019) found two stars which seem to be associated with the Chenab stream when looking for RRLs in that galaxy. With Gaia we recovered one of these stars (Chenab-V4), and we found another one (Gaia ID 6561477651849190912) with similar magnitude to Chenab-V4 but farther away from the center of Grus II, at 54 .…”
Section: Ufd Galaxies With No Gaia Rrlsmentioning
confidence: 93%
See 2 more Smart Citations